Utilization of leaves powder of Grewia asiatica (falsa) as an efficient bioadsorbent for the removal of Congo red from an aqueous solution - Muhammad Imran Khan; Abdallah Shanableh; Suryyia Manzoor; Nosheen Farooq; Ansa Madeeha Zafar; Djamel Ghernaout; Ramzi Hadj Lajimi; Mohamed.R. El-Aassar; Sarra Elgharbi; Shabnam Shahida; Mushtaq Hussain Lashari (Desalination and Water Treatment)
This research reports batch adsorption of Congo red (CR) dye from an aqueous solution onto leaves powder of Grewia asiatica (GA) at 25 °C. The influence of operational parameters on the percentage removal of CR was evaluated in detail. The percentage removal of CR was increased from 48 to 99%, 35 to 99%, and 51 to 77% at optimum contact time, amount of leaves powder of GA, ionic strength respectively whereas decreased from 99 to 45%, 99 to 66% and 96.1 to 92.2% with initial concentration of CR solution, temperature and pH, respectively. Adsorption kinetic results represented that CR adsorption onto leaves powder of GA fitted to pseudo-second-order kinetic model because the value of correlation coefficient was close to unity (R2 >0.999). Nonlinear isotherms such as Langmuir, Freundlich, Temkin and Dubinin-Radushkevich (D-R) were applied for CR adsorption onto leaves powder of GA. Results showed that CR adsorption followed nonlinear Langmuir isotherm due to lower value of chi-square test (χ2 = 7.84063 ×10−10). Adsorption thermodynamic study was conducted by measuring the change in Gibb’s free energy (ΔG°), entropy (ΔS°) and enthalpy (ΔH°). Results showed that CR adsorption onto leaves powder of GA was exothermic (ΔH= −106 KJ/mol) and spontaneous process. The regeneration of adsorbent was also illustrated.